2021
DOI: 10.1007/s10704-021-00545-8
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack growth behaviour of wire and arc additively manufactured ER70S-6 low carbon steel components

Abstract: The new emerging Wire and Arc Additive Manufacturing (WAAM) technology has significant potential to improve material design and efficiency for structural components as well as reducing manufacturing costs. Due to repeated and periodic melting, solidification and reheating of the layers, the WAAM deposition technique results in some elastic, plastic and viscous deformations that can affect material degradation and crack propagation behaviour in additively manufactured components. Therefore, it is crucial to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…It was noted that the material constant, m, calculated in this study lies within the range of 2 to 4 which is typically observed in the wrought material counterparts tested in the absence of corrosive media. 15 From the results presented in Figure 8B and Table 3, it has been observed that the location and orientation of the C(T) samples do not have a major influence on the FCG behavior of the ER70S-6 WAAM specimen with parallel-built deposition strategy.…”
Section: Fatigue Crack Propagation Testing and Analysismentioning
confidence: 85%
See 4 more Smart Citations
“…It was noted that the material constant, m, calculated in this study lies within the range of 2 to 4 which is typically observed in the wrought material counterparts tested in the absence of corrosive media. 15 From the results presented in Figure 8B and Table 3, it has been observed that the location and orientation of the C(T) samples do not have a major influence on the FCG behavior of the ER70S-6 WAAM specimen with parallel-built deposition strategy.…”
Section: Fatigue Crack Propagation Testing and Analysismentioning
confidence: 85%
“…The FCG rates obtained from the present study were further compared with an oscillation-built deposition strategy on the same material from the literature. 15 The C(T) samples in Ermakova et al 15 were tested in air at the same load ratio and P max . The comparison of the parallel-built and oscillation-built strategies has been presented in Figure 8 and Table 3.…”
Section: Fatigue Crack Propagation Testing and Analysismentioning
confidence: 99%
See 3 more Smart Citations